Epidermal Growth Factor Receptor Expression in Oral Squamous Cell Carcinoma by Immunohistochemical Technique and its Correlation with Clinicopathological Features - Zohreh Dalirsani; Bahram Memar; Atessa Pakfetrat; Nooshin Mohtasham; Kazem Anvari; Sara kaveh (Journal of Kerman University of Medical Sciences, 2020)
Background:Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral cavity. Despite some improvements in treatment, the survival rate is still very low, mainly due to the possible development of secondary malignancy or metastasis. Clinical and pathological features as well as molecular biomarkers might predict the recurrence. In recent years, many studies have been carried out on molecular biomarkers that can predict the prognosis of OSCC. One of these markers is the epidermal growth factor receptor (EGFR), which has led to different results. The aim of this study was to determine EGFR level in OSCC and to analyze its correlation with clinicopathological features. Methods: A total of 62 paraffin-embedded samples from OSCC patients treated in the oncology department of the Omid Hospital in the city of Mashhad, Iran were selected and EGFR staining was performed. The clinical and histopathological data were extracted from the medical records. Results: EGFR expression was positive in 98.4% of the cases. There was a significant difference between EGFR expression in the tumor and control cases in terms of cellularity and intensity (p˂0.001 and p=0.004, respectively). No statistically significant correlation was observed between EGFR and clinicopathological parameters. There was also no significant relationship between the cellularity and intensity expression of EGFR and patient survival (p=0.92 and p=0.42, respectively). Conclusion: In view of the high EGFR expression in squamous cell carcinoma, further studies on the role of EGFR in cell processes such as proliferation, angiogenesis and differentiation of the tumor are recommended.